Not a galaxy far, far away. A first look into the microhabitat of Romanogobio skywalkeri. (12th November 2021) - Witt, Christian; Friedrich, Thomas
Abstract: In October 2014, several specimens of Gobioninae were caught in the river Mur in Styria (Austria), later described as a new species of the genus Romanogobio. The species Romanogobio skywalkeri is to current knowledge endemic to the river Mur and of high conservation value. This study aims to investigate, for the first time, the microhabitat of R. skywalkeri in the upper river Mur. In winter 2016 and spring 2017 a sampling campaign was carried out to investigate the microhabitat of this species. In total, 60 adult and subadult individuals were caught. The microhabitat of these 60 individuals was assessed regarding water depth, flow velocity (v40 and v0) and substrate composition. R. skywalkeri at this point seems to be a highly rheophilic species with a narrow habitat preference. The preferred habitat found during our study consisted solely of riffle sections with fast flow velocity (0.45–1.3 m/s) and coarse substrate fractions, mostly meso‐ and macrolithal (6.3–40 cm). The current distribution range only covers about 100 km of the Mur between Fisching and Frohnleiten, which makes this endemic species highly vulnerable to habitat loss and alteration by anthropogenic impacts.